Patient-centred communication in the use of antidepressants among people with depression: a scoping review - Zaini, Syahrir; Sulaiman, Ahmad Hatim; Zaman Huri, Hasniza; Koh, Ong Hui; Gill, Jesjeet Singh; Francis, Benedict; Tan, Chok How; Azhar, Fatin Liyana; Ong, Jen Yeung; Lim, Kuok Quan; Zulkifli, Nathratul Ayeshah; Nair, Navin; et al. (UKM, 2021)
Antidepressants are the mainstay of depression treatment. However, little information is known about patient-centred communication related to the use of antidepressant among people with depression. This review aims to provide a comprehensive mapping of previously published studies on patient-centred communication in the use of antidepressants among patients with depression. A scoping review of the literature was conducted using PubMed, CINAHL, and Cochrane to answer the following questions: What is the nature of published scientific literature on this topic? and To what extent do the published articles address the six core components of patient-centred communication, which are: encouraging effective clinician-patient relationships, obtaining and providing information, responding to emotional states, handling uncertainty, achieving the best decision as well as advocating patient self-management? Out of 494 records identified, a total of 13 articles were included in the scoping review (2 randomised controlled trials, 1 observational cohort study, 5 cross-sectional studies, 4 qualitative studies, and 1 review article). All 6 core components of the patient-centred communication were discussed extensively in the literature except for 2 of them, which were handling uncertainty and patient self-management. Shared decision making (SDM) was found to be a critical feature in patient-centred communication. The six core components of patient-centred communication have been consistently recognized as vital for the process of achieving patient-centred care. SDM can be included as a tool to assist clinicians and patients in addressing effective clinician-patient relationships.